Gating and Regulatory Mechanisms of TMEM16 Ion Channels and Scramblases - Le, Son C.; Liang, Pengfei; Lowry, Augustus J.; Yang, Huanghe (Frontiers in Physiology, 2021)
The transmembrane protein 16 (TMEM16) family consists of Ca2+-activated ion channels and Ca2+-activated phospholipid scramblases (CaPLSases) that passively flip-flop phospholipids between the two leaflets of the membrane bilayer. Owing to their diverse functions, TMEM16 proteins have been implicated in various human diseases, including asthma, cancer, bleeding disorders, muscular dystrophy, arthritis, epilepsy, dystonia, ataxia, and viral infection. To understand TMEM16 proteins in health and disease, it is critical to decipher their molecular mechanisms of activation gating and regulation. Structural, biophysical, and computational characterizations over the past decade have greatly advanced the molecular understanding of TMEM16 proteins. In this review, we summarize major structural features of the TMEM16 proteins with a focus on regulatory mechanisms and gating.